Geographical mobility of young people in rural Spain at the turn of the century: evolution of expectations between 1997 and 2012 - Gastón-Faci, Diego; Minguijón-Pablo, Jaime; Tomás del Río, Eva (Acciones e Investigaciones Sociales, 2019)
In recent decades, rural emigration has started to wane in Spain, although in many places there is still an exodus of young adults, which makes it difficult for many towns to survive and often determinesthe expectations of new generations. The aim of this study is to see how the expectations of geographical mobility have evolved among Spanish adolescents residing in rural areas, in four different phases between 1997 and 2012. This analysis focuses on how minors perceive and intend to build their future, and also in the difficulties they imagine they might en- counter along the way. Qualitative methodology has been designed as a result of the need to apply an exploratory approach that is both inductive and descriptive in nature. In particular, the methodology followed was si- milar to the one used by Bernot and Blancard (1953) and entailed analy- sing the content of school essays written by pupils of 13-15 years of age, who were in their second year of secondary education (known as ESO in Spain) and were asked to write on the following topic: “Assuming that you may live to the age of 100, how do you see your future, starting with your immediate future and running through adolescence, adulthood and later life?” 872 essays were studied throughout the four phases of the research, from more than 100 schools all over the country. The essays were done in class as just another academic activity set by the teaching staff at the various educational establishments, following the methodological instruc- tions given. From the research it is concluded that territorial mobility would not be one of the adolescents’ main concerns throughout the entire period under study, despite the fact that their migration prospects may well have increased: there is a greater preference for short-haul mobility in all stages of the study; from 2008 onwards emigration overseas starts to be obser- ved: or else a significant number of minors wish to return to their place of origin once they have finished their training. Social control will no longer be a determining factor in deciding whether to emigrate, in the enquiries made after 2007.
Keywords: rural migration; rural planning; student sociology; adolescence; rural youth; rural sociology; social control